A literary holiday cookbook : festive meals for the Snow Queen, Gandalf, Sherlock, Scrooge, and book lovers everywhere - Walsh, Alison (Food writer) (Skyhorse Publishing, 2020)
"Some of the most famous instances of fictional fare have become synonymous with the holidays. Who can forget the plentiful food surrounding the Ghost of Christmas Present in A Christmas Carol? The simple but generous and joy-filled Christmas gatherings at the Marchs' in Little Women? Or the Van Tassel's autumnal feast in The Legend of Sleepy Hollow? Finally, these literary meals can become a reality on your table with A Literary Holiday Feast. From Christmas and Thanksgiving to Halloween and New Year's, this seasonal cookbook offers 17 full four-course holiday meals from 25 classic books- each including an appetizer, entrée, side dish, and dessert. Additionally, whip up festive sips and delectable edible gifts to share with loved ones."--Amazon.